Values of woman academician towards career success and recognition : a case-study in Universiti Malaysia Sarawak (UNIMAS) - Stephanie, Anak Fossillian (Universiti Malaysia Sarawak (UNIMAS), 2011)
This study aims to identify the values towards career success and recognition among women academician. The study was conducted in University Malaysia Sarawak (UNIMAS). Quantitative method was used and five Likert-scale questionnaires were distributed to the respondents. 55 respondents were involved in this study. This study was conducted to determine the relationship between factors which consists of demographic factors, attitudinal factors, and resources factors of women academician towards career success and recognition. Demographic characteristics of the respondents which included age group, marital status and academic rank were analyzed to determine the significant relationship and respondents' values towards career success and recognition by using One-way ANOVA and Independent Samples T-test. The relationship between attitudinal factors and resources factors of women academicians towards career success and recognition were tested by using Pearson Correlation Coefficient. Multiple regressions were carried out to determine the most dominant factors. The results showed that there were significant relationship between demographic factors, attitudinal factors, and resources factors of women academicians towards career success and recognition. Based on these fmdings, several recommendations were presented to the organization, human resource practitioners, future researchers and academicians. Organization should focus on providing the needs especially to women academicians so that there are no limited resources to career success and having recognized. Besides that, human resource practitioners should be more sensitive and fair in managing the people's need. For future researchers, it is suggested to carry out study which involves more than one higher educational institution. For women academicians themselves should identify resources that helps them towards career success and recognition.